Determinan Keluhan Musculosceletal Disorders Pada Penenun Sarung Sutera Di Kecamatan Tanasitolo Kabupaten Wajo - Muh Kahfi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2023)
One of the problems among silk sarong weavers is complaints of Musculoskeletal Disorders (MSDs), namely the emergence of muscle complaints due to unergonomic work attitudes. Complaints that are felt include the muscles of the neck, shoulders, arms, hands, fingers, back, waist and lower muscles. The aim of this research is to determine the factors associated with MSDs complaints among silk sarong weavers in Pakanna Village, Tanasitolo District, Wajo Regency. This research is a quantitative study, using a cross sectional study approach, with a population of 124 people and a sample of 42 people selected using purposive sampling. Work posture risk assessment uses the REBA method and measurement of the level of MSDs complaints using the Nordic Body Map questionnaire. The research results showed that of the 42 respondents there were 37 (88.1%) with medium work posture risk, and 5 (11.9%) with high work posture risk. Meanwhile, for MSDs complaints, there were 21 (50.0%) who suffered from moderate MSDs complaints, 11 (26.2%) who suffered from mild MSDs complaints, and 10 (23.8%) who suffered from severe MSDs complaints. Based on the results of the chi-square test, it shows that there is a relationship between MSDs complaints and work posture (p value = 0.005), age (p value = 0.013), work period (p value = 0.002), length of work (p value = 0.000), history of illness. (p value = 0.000). Therefore, workers are advised to rest when they start to feel pain or soreness in any part of their body, and diligently stretch their muscles while working. Relevant agencies should provide education regarding work risks and work procedures in accordance with ergonomic principles.